2018
DOI: 10.4274/tjh.2018.0119
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ischemia Modified Albumin Levels and Dynamic Thiol / Disulfide Balance in Sickle Cell Disease

Abstract: Objective:Sickle cell disease (SCD), described as a group of inherited blood disorders, affects millions of people throughout the world and is particularly common in the southern part of Turkey. We aimed to determine the relationship between ischemia-modified albumin (IMA) and the dynamic thiol/disulfide balance in SCD.Materials and Methods:Fifty-four adult SCD patients and 30 healthy controls were included in the study. The 54 adult patients included 30 (56%) males and 24 (44%) females with a mean age of 28.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Although it has been shown that thiols play a role in the pathogenesis of many disease, such as ankylosing spondylitis, lung cancer, rheumatoid arthritis, diabetic nephropathy, sickle cell disease, gastric cancer, and juvenile idiopathic arthritis [15][16][17][18][19][20][21], few studies have been conducted with respect to sepsis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that thiols play a role in the pathogenesis of many disease, such as ankylosing spondylitis, lung cancer, rheumatoid arthritis, diabetic nephropathy, sickle cell disease, gastric cancer, and juvenile idiopathic arthritis [15][16][17][18][19][20][21], few studies have been conducted with respect to sepsis [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Although the sensitivity of the D-dimer test is high, its specificity is low (24,27). In several studies, it was reported that IMA is a more sensitive test, compared with D-dimer, in the diagnosis of PE (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia-modified albumin (IMA) is formed by albumin modification caused by reactive oxygen derivatives due to ischemia. IMA is used as a sensitive biochemical marker of ischemia and oxidative stress caused by tissue hypoxia (23,24). In previous studies, it was reported that IMA levels increase among patients with ischemia, acute rheumatic fever, hepatic failure, chronic obstructive pulmonary disease (COPD) and cerebro-vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Disulfide structures (S-S), which are formed as a result of OS are reduced to thiol groups again, and thiol balance is achieved 12. In many studies, the measurement of dynamic thiol disulfide balance has been shown as an indicator of increased free radical levels in various diseases 13–16. The increase in OS causes free radical damage at the N-terminal end of albumin molecules and decreases the binding capacity of albumin.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in OS causes free radical damage at the N-terminal end of albumin molecules and decreases the binding capacity of albumin. The modified form of albumin is called ischemia-modified albumin (IMA) and is used a responsive marker of OS 13. To the best of our knowledge, this is the first study to evaluate both dynamic thiol-disulfide hemostasis and IMA levels in patients with CLL.…”
Section: Introductionmentioning
confidence: 99%